THE INFLUENCE OF COMPANY WEALTH ON THE ABILITY TO GENERATE PROFITS IN THE BANKING INDUSTRY IN INDONESIA 2015-2019 - Ignatius Oki Dewa Brata; Sendi Gusnandar Arnan; Mohd Haizam Saudi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to determine how ability to generate profits is influenced by company assets in the banking sector during the period 2015-2019. The data analysis used is multiple regression by first performing a classical assumption test, where all banks in the banking sector listed on the Indonesia Stock Exchange are all sampled. The results showed that one off Asset indicator has a significant effect in a with ability to generate profits, while the other has no significant effect in a positive direction with ability to generate profits, the model test shows that both Indicator together have an effect on ability to generate profits. Keywords: Assets, Banking Industry, Profit, Performance.